Leaky Pipeline Myths: In Search of Gender Effects on the Job Market and Early Career Publishing in Philosophy - Allen-Hermanson, Sean (Frontiers in Psychology, 2017)
That philosophy is an outlier in the humanities when it comes to the underrepresentation of women has been the occasion for much discussion about possible effects of subtle forms of prejudice, including implicit bias and stereotype threat. While these ideas have become familiar to the philosophical community, there has only recently been a surge of interest in acquiring field-specific data. This paper adds to quantitative findings bearing on hypotheses about the effects of unconscious prejudice on two important stages along career pathways: tenure-track hiring and early career publishing.